Midlife insulin resistance, APOE genotype, and late-life brain amyloid accumulation. (27th March 2018) - Ekblad, Laura L.; Johansson, Jarkko; Helin, Semi; Viitanen, Matti; Laine, Hanna; Puukka, Pauli; Jula, Antti; Rinne, Juha O.
Abstract : Objective: To examine whether midlife insulin resistance is an independent risk factor for brain amyloid accumulation in vivo after 15 years, and whether this risk is modulated by APOE ε4 genotype. Methods: This observational study examined 60 elderly volunteers without dementia (mean age at baseline 55.4 and at follow-up 70.9 years, 55.5% women) from the Finnish population-based, nationwide Health2000 study with [ 11 C]Pittsburgh compound B–PET imaging in 2014–2016. The participants were recruited according to their homeostatic model assessment of insulin resistance (HOMA-IR) values in the year 2000, and their APOE ε4 genotype. The exposure group (IR+, n = 30) consisted of individuals with HOMA-IR >2.17 at baseline (highest tertile of the Health2000 study population), and the control group (IR−, n = 30) consisted of individuals with HOMA-IR <1.25 at baseline (lowest tertile). The groups were enriched for APOE ε4 carriers, resulting in 50% (n = 15) APOE ε4 carriers in both groups. Analyses were performed with multivariate logistic and linear regression. Results: An amyloid-positive PET scan was found in 33.3% of the IR− group and 60.0% of the IR+ group (odds ratio 3.0, 95% confidence interval 1.1–8.9, p = 0.04). The increased risk was seen in carriers and noncarriers of APOE ε4 genotype. Higher midlife, but not late-life continuous HOMA-IR was associated with a greater brain amyloid burden at follow-up after multivariate adjustments for other cognitive and metabolic risk factors (β = 0.11, 95% confidence interval 0.002–0.22, p = 0.04). Conclusions: These results indicate that midlife insulin resistance is an independent risk factor for brain amyloid accumulation in elderly individuals without dementia.